5 Reasons Why Scoliosis X-Rays Are Not Harmful - Paul A. Oakley DC, MSc; Niousha Navid Ehsani MD; Deed E. Harrison DC (SAGE Publishing, 2020)
Radiographic imaging for scoliosis screening, diagnosis, treatment, and management is the gold standard assessment tool. Scoliosis patients receive many repeat radiographs, typically 10-25 and as many as 40-50, equating to a maximum 50 mGy of cumulative exposure. It is argued this amount of radiation exposure is not carcinogenic to scoliosis patients for 5 main reasons: 1. Estimated theoretical cumulative effective doses remain below the carcinogenic dose threshold; 2. Scoliosis patient x-rays are delivered in serial exposures and therefore, mitigate any potential cumulative effect; 3. Linear no-threshold cancer risk estimates from scoliosis patient cohorts are flawed due to faulty science; 4. Standardized incidence/mortality ratios demonstrating increased cancers from aged scoliosis cohorts are confounded by the effects of the disease entity itself making it impossible to claim cause and effect resulting from low-dose radiation exposures from spinal imaging; 5. Children are not more susceptible to radiation damage than adults. Radiophobia concerns from patients, parents, and doctors over repeat imaging for scoliosis treatment and management is not justified; it adds unnecessary anxiety to the patient (and their parents) and interferes with optimal medical management. X-rays taken in the evidence-based management of scoliosis should be taken without hesitation or concern about negligible radiation exposures.